Leitura literária e ensino de língua estrangeira: o conto de Edgar Allan Poe no processo de ensino e aprendizagem de língua inglesa no ensino médio - Santos, Rosana Alves Simão dos (2017)
This research is a case study entitled Literary reading and Foreign Language teaching: the Edgar Allan Poe short story in the process of the teaching and learning of the English Language in High School, and it stems from the line of research “Theoretical-methodological Conceptions and Teaching Conceptions”. Its objective is to investigate and to describe the rippling influences of a literary text (authentic material) as a didactic material. The guiding question to this study was: what are the contributions of a literary text (authentic materials) as a didactic resource to the process of teaching and learning of a foreign language as well as to students’ motivation? The corpus of the research was the short story “the Black Cat” by American author, Edgar Allan Poe. The collecting of the data happened during a didactic sequence (DS) with students in the 1st year of High School in a public institution in the city of Trindade- GO, their ages ranging from 14 and 16 years old. For the data analysis, two questionnaires were used, one initial questionnaire and a final questionnaire, and the activities carried out during the DS. This study was based on theories on the Short Story, Literature and didactic materials, using some of the following authors: (1994), Calvino (1990), Candido (1995, 2004), Campagnon (2009), Eco (2003), Duarte (2016), Leffa (1999), Pessoa (2009), Almeida Filho (2013), Almeida Filho e Barbirato (2000), amongst others. The analysis adumbrated that the practice of literary readings and the utilization of authentic materials in the foreign language classroom can motivate and contribute, in a positive way, to the teaching and learning process. Thus, we hope that this work can be a rich source of information to the pedagogic practices of other foreign language (FL) teachers, since there is not only the improvement of pedagogical practices, but also the value of theoretical reflection.